Allergen immunotherapy: The growing role of observational and randomized trial "Real‐World Evidence". Issue 9 (31st August 2021) - Paoletti, Giovanni; Di Bona, Danilo; Chu, Derek K.; Firinu, Davide; Heffler, Enrico; Agache, Ioana; Jutel, Marek; Klimek, Ludger; Pfaar, Oliver; Mösges, Ralph; DunnGalvin, Audrey; Genuneit, Jon; et al.
Abstract: Background: Although there is a considerable body of knowledge about allergen immunotherapy (AIT), there is a lack of data on the reliability of real‐world evidence (RWE) in AIT, and consequently, a lack of information on how AIT effectively works in real life. Methods: To address the current unmet need for an appraisal of the quality of RWE in AIT, the European Academy of Allergy and Clinical Immunology Methodology Committee recently initiated a systematic review of observational studies of AIT, which will use the RELEVANT tool and the Grading of Recommendations Assessment, Development and Evaluation approach (GRADE) to rate the quality of the evidence base as a whole. The next step will be to develop a broadly applicable, pragmatic "real‐world" database using systematic data collection. Based on the current RWE base, and perspectives and recommendations of authorities and scientific societies, a hierarchy of RWE in AIT is proposed, which places pragmatic trials and registry data at the positions of highest level of evidence. Key Results: There is a need to establish more AIT registries that collect data in a cohesive way, using standardized protocols. Conclusions: This will provide an essential source of real‐world data that can be easily shared, promoting evidence‐based research and quality improvement in study design and clinical decision‐making.